Impact of fluoroquinolone and heavy metal pollution on antibiotic resistance maintenance in aquatic ecosystems - Emilie Dehon; Stanislava Vrchovecká; Alban Mathieu; Sabine Favre-Bonté; Stanisław Wacławek; Arnaud Droit; Timothy M. Vogel; Concepcion Sanchez-Cid (Environmental Microbiome)
Abstract Background Freshwater pollution with compounds used during anthropogenic activities could be a major driver of antibiotic resistance emergence and dissemination in environmental settings. Fluoroquinolones and heavy metals are two widely used aquatic pollutants that show a high stability in the environment and have well-known effects on antibiotic resistance selection. However, the impact of these compounds on antibiotic resistance maintenance in aquatic ecosystems remains unknown. In this study, we used a microcosm approach to determine the persistence of two fluoroquinolones (ciprofloxacin, ofloxacin) and two heavy metals (copper and zinc) in the Rhône river over 27 days. In addition, we established links between antibiotic and metal pollution, alone and in combination, and the composition of freshwater bacterial communities, the selection of specific members and the selection and maintenance of antibiotic and metal resistance genes (ARGs and MRGs) using a metagenomics approach. Results Whereas ofloxacin was detected at higher levels in freshwater after 27 days, copper had the strongest influence on bacterial communities and antibiotic and metal resistance gene selection. In addition, heavy metal exposure selected for some ARG-harboring bacteria that contained MRGs. Our research shows a heavy metal-driven transient co-selection for fluoroquinolone resistance in an aquatic ecosystem that could be largely explained by the short-term selection of Pseudomonas subpopulations harboring both fluoroquinolone efflux pumps and copper resistance genes. Conclusion This research highlights the complexity and compound-specificity of dose-response relationships in freshwater ecosystems and provides new insights into the medium-term community structure modifications induced by overall sub-inhibitory levels of antibiotic and heavy metal pollution that may lead to the selection and maintenance of antibiotic resistance in low-impacted ecosystems exposed to multiple pollutants.